Lignin Degradation of Kapok Fiber (Ceiba pentandra, L) with Different Times of Pulping - Fransiska Angelina Rezekinta; Anwar Kasim; Edi Syafri; Irawati Chaniago; Firman Ridwan (Journal of Applied Agricultural Science and Technology, 2023)
Lignin reduced the adhesion between the polymeric matrix and natural reinforcement in composite materials by its hydrophobic characteristic. Removal of lignin can be a solution to improve fiber function in composite use. This study aimed to determine the degradation of lignin at different times of pulping. The soda process was conducted at 60, 70, 80, 90, and 100 minutes of pulping using heat in a room atmosphere. Yields, lignin content, and lignin spectrum (FT-IR analysis) were measured.  The result showed the highest degradation of lignin was in 100 minutes of pulping with 80.34% lignin degradation and 3.57% lignin left in fibers. However, the yield of fibers decreased with increasing pulping time due to lignin removal. 100 minutes of pulping time showed the highest loss of fiber yield. This study showed the best pulping time for kapok fiber is 100 minutes with 3.57 % lignin remaining in the pulp.